Hyponatremia and weight changes in an ultradistance triathlon - Speedy, D. B.; Faris, J. G.; Hamlin, M.; Gallagher, P. G.; Campbell, R. G. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: To describe the weight changes and the incidence of hyponatremia during an ultradistance triathlon in the athletes who attend medical care after the race. DESIGN: Descriptive research. SETTING: The 1996 New Zealand Ironman Triathlon in which each athlete swam 3.8 km, cycled 180 km, and ran 42 km. PARTICIPANTS: Ninety-five athletes attending for medical care after the race were studied. One hundred sixty-nine athletes who did not attend for medical care were also weighed before and after the race. MAIN OUTCOME MEASURES: Weights were measured at race registration and on finishing the race. Whole-blood sodium concentration was measured in those athletes with clinical evidence of fluid or electrolyte disturbances. RESULTS: Weights were significantly decreased at the end of the race in the athletes seeking medical care (n = 48, mean % delta wt = -2.5%, p < 0.001) and also in the athletes who did not seek medical care (n = 169, mean % delta wt = -2.9%, p < 0.001). Seventeen percent of race starters sought medical attention. Dehydration accounted for 26% of primary diagnoses and hyponatremia for 9%. One athlete with hyponatremia (Na 130 mEq/L) is described who drank 16 L over the course of the race, with a weight gain of 2.5 kg. This is consistent with the hypothesis of fluid overload as the cause of his hyponatremia. Hyponatremia accounted for four of five admissions to the hospital after the race. An inverse relationship between postrace sodium concentrations and percentage change in body weight was observed (r = -0.63). CONCLUSIONS: Hyponatremia is an important risk to the health of athletes competing in an ultradistance triathlon, with fluid overload the likely aetiology.